Genetic algorithm for material cost minimization of external strengthening system with fiber reinforced polymer - Rahman, M.M.; Jumaat, Mohd Zamin; Hosen, M.A. (2012)
An optimization procedural method for designing fiber reinforced polymer (FRP) plate for strengthening reinforced concrete beam is presented. The optimization procedure is formulated to find the design variables leading to the minimum cost of structural strengthening system using CFRP plate with constraints imposed based on TR55 code provisions. Genetic algorithm based approach is utilized to solve the optimization task. The cost of FRP plate and epoxy adhesive is included in the formulation of the objective function. The ultimate limit states and the serviceability limit states are included in formulation of constraints. A numerical example is given to show the validity of the proposed optimization method.